APPLICATION OF INDIVIDUAL COMPETITIVITY IN SALES FORCE MANAGEMENT: IMPLICATIONS AND STRATEGIES - Zaenal Aripin; Nyoman Dwika Ayu Amrita; Wawan Ichwanudin (Journal of Jabar Economic Society Networking Forum, 2024)
In the competitive business era, individual competitiveness in sales force management has become an important focus for companies to achieve success. Developing effective strategies to implement individual competitiveness can have significant implications for a company's performance and position in the market. This research aims to investigate the implications of implementing individual competitiveness in sales force management and to identify effective strategies for increasing individual competitiveness in the sales environment. The research method used in this research is qualitative, by conducting an in-depth literature review to understand the basic concepts, implications and strategies for implementing individual competition in sales force management. The research results show that the application of individual competitiveness in sales force management has a significant impact on individual performance, company revenue growth, and position in the market. Implementation strategies such as intensive training, proper motivation, and effective performance management can help increase the individual competitiveness of sales employees and strengthen the company's position in the competitive market.